Effects of Bobath and Neurodevelopmental Treatment in A 3.5 Years Old Child with Lacunar Pure Motor Stroke Following Ventricular Septal Defect Repair: Bobath and Neurodevelopmental Treatment in A Child with Lacunar Pure Motor Stroke - Khuram, Nayab; Afzal, Binash; Nasir, Rida; Mushtaq, Hafza (Pakistan Journal of Health Sciences, 2022)
Lacunar pure motor stroke happens when an artery leading to the deep section of the brain, which contains the organs like the thalamus or basal ganglia is obstructed. Small and occurring outside of the cortex, lacunar strokes are a subtype of ischemic stroke. Lacunar strokes mostly affect patient’s memory, judgmental skills and language. On the basis of symptoms, lacunar stroke is categorized as pure motor hemiparesis (45% cases), pure sensory stroke (7% cases) and ataxic hemiparesis (17-18% cases). We reported a case of 3.5 years old male patient with pure motor lacunar stroke following ventricular septal defect repair who was effectively treated with bobath therapy and neurodevelopmental therapy as bobath is a generally accepted theory in the rehabilitation of hemiparetic stroke victims worldwide. On examination, the patient had a total pure motor based right sided hemiparesis. The lower extremity movements were more compromised than upper extremity, strength of mainly antigravity or postural muscles was compromised and lower extremity muscles were scoring 1/5 on Manual Muscle Testing (MMT) and scored 1 on Modified Ashworth Scale (MAS). As such there was no spasticity factor in the upper or lower limb muscles but there was weakness (right sided hemiparesis), so the treatment plan was given and thoroughly explained to the patient’s caretaker. There was no major cognitive and sensory deficit, as lacunar stroke has a better prognosis than other types of stroke, so, the recovery was good within 3 to 4 months by NDT and bobath therapy. Bobath therapy mainly improves the motor function with postural balance and stability.